IDENTIFIKASI MISKONSEPSI SISWA PADA MATERI FOTOSINTESIS DAN RESPIRASI - Putri Sulamtina; Tri Jalmo; Berti Yolida (Universitas Lampung, 2017)
The aim of this research was to know misconceptions of VIIIth grade students on photosintetic and respiration subject and the factors that affected students misconception at Jatiagung. The samples were 282 students that selected using purposive sampling technique. The design used simple descriptive research.. The quantitative data were obtained from the students' answer and interpreted into criteria. The qualitative data were factors that affected the studentss misconceptions that were obtained from questionnaire and analyzed using Pearson Product Moment Test Correlational. The result showed that the level of misconceptions was